Effect of Basil (Ocimum sanctum Linn) Leaf Extract As Repellent Against Mosquito Aedes aegypti - Aulia, Nur; Hamzah, Baharuddin; Ningsih, Purnama (Jurnal Akademika Kimia, 2019)
Study on the effect of basil (Ocimum sanctum Linn) leaf extract has been done as a repellent against mosquito (Aedes aegypti). This study aimed to examine the effect of basil leaf extract on Aedes aegypti using an electrical device. This study usedan extraction method with ethanol 96%solvent followed by evaporation to obtain concentrated basil leaf extract. The concentrated extract was diluted to concentrations of 20, 30, 40 and 50% w/v. The results showed that the concentration of basil leaf extract 50% eliminatedmost mosquitoes (Aedes aegypti).